Determination of Employee Performance: Work Discipline, Work Environment and Leadership (Literature Review) - Eko Suprapto; Amalina Maharani (Dinasti Research, 2021)
Employee performance has a very important role in the organization, because employee performance is the end result of the employee's performance process in completing their duties. The purpose is to determine and analyze the effect of Work Discipline on Employee Performance. To find out and analyze the influence of the Work Environment on Employee Performance. To find out and analyze the influence of Leadership on Employee Performance. This article reviews the Determination of Employee Performance: Work Discipline, Work Environment and Leadership. The results of this research library are that: 1). The Influence of Work Discipline on Employee Performance, 2). The Effect of Work Environment on Employee Performance, and 4). The Effect of Leadership on Employee Performance.